Sistem Kontrol dan Monitoring AC dengan Menggunakan Metode Fuzzy Mamdani Berbasis IoT - Ginting, Meiliyani Br; Sinuhaji, Nirwan; Tarigan, Ita Margaretta Br (Journal of Information System Research (JOSH), 2024)
The problem of hot air temperature can disrupt indoor comfort and energy efficiency. The use of AC as a solution to cool the room is often not optimal, with problems such as AC remaining on when the room is empty and arbitrary temperature settings, which can accelerate device damage. To overcome this problem, this study proposes the development of an AC control and monitoring system that utilizes the Fuzzy Mamdani method based on the Internet of Things (IoT). The Fuzzy Mamdani method was chosen because of its ability to handle uncertainty and variability in temperature settings, while IoT allows the system to monitor and control the AC in real-time via the internet. The proposed system is designed to monitor the condition of the AC, automatically adjust the temperature based on actual needs, and provide information for corrective action if necessary. With this system, it is expected that the use of AC can be optimized, energy efficiency increased, and the service life of the AC can be extended. This study shows the importance of implementing a Fuzzy Mamdani and IoT-based control system to overcome the suboptimal use of AC, improve comfort, and reduce energy consumption. The results of this study are expected to make a significant contribution to more efficient AC management in educational environments and can be a model for similar applications in other fields. From the results, the room temperature tested was 25°C with humidity reaching 80%. Based on data processing using the Fuzzy Mamdani method, the results of the decision for the recommended AC temperature were 23.3°C. These results are in accordance with the results of manual testing.